2021
DOI: 10.1097/nnd.0000000000000789
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Assessing a Competency-Based Nurse Orientation in Pediatric Ambulatory Infusion Clinics

Abstract: Clinical nurse competency can be well supported through the institution of competency-based nurse orientation programs. The aims of this quality improvement project are twofold: to develop an orientation checklist that contains competency-based education techniques and assessment tools and to evaluate the usability of the competency-based orientation checklist by nursing staff. The project used a pre-post survey design to assess usability. The findings demonstrate that competency-based education and assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Checklists have shown potential value and benefit for human intensive and multi-step procedures with high complexity, so as to promote consistency and completeness to carry out specific tasks. Apart from surgical procedures, it has also been adopted in nursing skills training [ 8 , 9 ], emergency life support training [ 10 , 11 ], and in other forms of medical teaching activities [ 12 ]. These studies share one concept in common, that is, although the content of the checklist is designed by investigators or instructors, the checklist yield benefit and values for users themselves by means of self-evaluation and self-reflection, which is in accordance with the intention of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Checklists have shown potential value and benefit for human intensive and multi-step procedures with high complexity, so as to promote consistency and completeness to carry out specific tasks. Apart from surgical procedures, it has also been adopted in nursing skills training [ 8 , 9 ], emergency life support training [ 10 , 11 ], and in other forms of medical teaching activities [ 12 ]. These studies share one concept in common, that is, although the content of the checklist is designed by investigators or instructors, the checklist yield benefit and values for users themselves by means of self-evaluation and self-reflection, which is in accordance with the intention of our study.…”
Section: Discussionmentioning
confidence: 99%
“…A literature search found that most survey instruments focused on NLRNs' experience, program assessment, or transitions into specialty practice settings. [17][18][19][20] Consequently, the research team used these findings to tailor items specific to ERNs to meet the study goals. [19][20][21] Cognitive interviews were conducted among four expert nurses to review and assess the conceptual similarity, accuracy, and clarity of the items (see Table 1).…”
Section: Data Collectionmentioning
confidence: 99%
“…The training model of competency-based training (CBT) is based on the key competency characteristics of the job. Under the guidance of job competency, scientific and reasonable training is carried out, and an effective operating mechanism is used as a guarantee to finally achieve the goal of improving personnel competence [ 9 ].…”
Section: Introductionmentioning
confidence: 99%